Pengaruh budaya organisasi dan komitmen organisasi terhadap kinerja karyawan - Helmy Choiriyanto; Mohammad Shohib (Cognicia, 2024)
Healthcare services in hospitals are a significant concern in Indonesia, where the quality of employee performance is often considered suboptimal. This may be influenced by cultural factors and levels of employee commitment. This study aims to examine the impact of organizational culture and organizational commitment on employee performance in hospitals, both individually and collectively. The research adopts a quantitative correlational approach. Research subjects were selected using purposive sampling techniques, with data obtained from 167 hospital employees in Lamongan. The study utilized scales measuring employee performance, organizational culture, and organizational commitment. Data analysis was conducted using multiple linear regression. The results indicate that organizational culture and organizational commitment together have a significant effect on employee performance, with an F value of 15.864 and a p-value less than 0.000, contributing an effective contribution of 16.2%. However, the partial effect analysis reveals that while organizational culture influences employee performance, organizational commitment does not significantly affect employee performance.